Mixed formulation solution and optical based experimental methods in the deformation analysis of radially loaded cylindrical shells - Madureira, L. R. (2011)
A mixed formulation in the characterization of internal forces and displacements in cylindrical shells, subjected to radial forces is presented. This numerical approach is proposed as an alternative to the irreducible formulation, where in some problems this solution leads to stress distribution presenting some discontinuity along the edge joining shell modules with different geometry as, for example, curved pipes with tangent terminations. The mixed formulation here proposed prescribes the continuity in the stress field at shell adjacent sections, while practically ensures similar accuracy in the displacement and stress fields. The force and displacement formulations are carried out by combining unknown analytic functions with trigonometric expansions. The solution can be applied to recurrent problems in piping design as is the case of edge forces and radial loads. Examples considering these external parameters are developed and results are compared with an experimental method based on optical interferometric techniques. These procedures were applied with video recording of the interferometric pattern and allow the displacement field assessment with a non-contact procedure.